The effect of the training program using technique (Acrylics Poring) on the on developing drawing skills of students in the department of art education - Awaz Mirza Faraj; Sabir Bakr Mustafa (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
This research is elicited from a Ph.D. thesis entitled (The effect of the training program using (Acrylics Poring) technique on the development of drawing skills among students in the Department of Art Education). The research aims to prepare a training program in the field of drawing and to know the effect of the training program on drawing skill. The study sample consisted of (17) students in the fourth stage who were randomly selected from the study population. The purpose of preserving its balance and defining one way for all students, the research sample and adjusting the variables, the two researchers equalized the research sample in the variables (pre-test, age of the students in the month, the degree of the topic of composition in the drawing for the year (2022-2023), the level of intelligence by conducting an intelligence test (IQ test)). The researchers conducted a questionnaire to formulate and build the training program, a questionnaire to determine modern drawing techniques, a questionnaire to prepare an evaluation card to evaluate the results of the research sample tests. After formulating and building the training program and receiving the opinion of experts according to a number of steps through which the training programs, its needs and objectives were determined. The researchers applied the training program using (Acrylics Poring) technology on the research sample for a period of (8) weeks, each week (1) lesson, each lesson (3) hours. After collecting the data and statistical analysis of the results, the two researchers reached a set of results, including building a training program step by step and then applying it to the research sample, and the emergence of a statistically significant effect between the average scores of achievement in the pre-test and post-test as a result of using the technique (Acrylics Poring), which means that the students of the research sample improved their level of drawing skills after an experiment. In light of the results, the researcher made a number of recommendations and proposals that he believes will complement his current research in the future